Analysis of dynamic characteristics of the active filter-stabilizer - Shcherbak, Yakov; Semenenko, Yuriy; Semenenko, Alexandr (Eastern-European Journal of Enterprise Technologies, 2017)
At the railway sections with intensive and high-speed train traffic, it is advisable to use active stabilizer-filters to increase efficiency of DC traction power supply systems. They are introduced into converter units of traction substations to ensure active filtration and stabilization of the output voltage. The active filter stabilizer consists of a voltage converter based on a capacitive energy storage unit and is connected in series with the main rectifying unit of the traction substation. The voltage converter with a two-way pulse-width modulation simultaneously forms a voltage for compensating harmonics and deviations of the mean value of the rectified voltage with respect to the specified voltage. It was established that the voltage converter of the active filter-stabilizer with two-way pulse width modulation for small values of the control signal increment is an amplitude-pulse second-order modulator. In this converter, information is transferred by two channels having static and dynamic transfer coefficients. Dynamic connection between the increments of the input and output signals of the active filter-stabilizer converter is of a variable character at each interval of discreteness of the pulse-width modulation. This property of the voltage converter is called forth by the changes in the static and dynamic transfer coefficients which must be taken into account when describing dynamic processes in closed-loop automatic control systems.